Enhancer recruitment of a RUNX1, HDAC1 and TLE3 co-repressor complex by mis-expressed FOXC1 blocks differentiation in acute myeloid leukemia - Fabrizio Simeoni; Tim CP Somervaille (Molecular & Cellular Oncology, 2021)
Tissue-inappropriate expression of FOXC1 (Forkhead Box C1) in acute myeloid leukemia confers a monocyte/macrophage lineage differentiation block. We discovered that FOXC1 interacts with RUNX1 (Runt-Related Transcription Factor 1) to stabilize a RUNX1, HDAC1 (Histone Deacetylase 1) and TLE3 (Transducin-like enhancer protein 3) repressor complex at enhancers controlling myeloid differentiation genes.